A comparative study between transbronchial cryobiopsy vs forceps biopsy in patients with interstitial lung diseases guided by fluoroscope - Mahmoud Abdelnasser Elkomy; Mohamed Samy Torky; Ayman Mohamed El Saqa; Hoda Mokhtar Bahr (The Egyptian Journal of Bronchology)
Abstract Background With a low incidence of complications and a high diagnostic yield, transbronchial cryobiopsy (TBCB) is a novel technique of lung biopsy especially for the diagnosis of interstitial lung diseases (ILDs). The objective of this research was to compare cryobiopsy and forceps biopsy with fluoroscopy guidance in ILDs regarding diagnostic yield, quality of samples, and associated complications. Methods This randomized controlled interventional study, which took place at the Faculty of Medicine’s Chest Department from December 2022 to August 2024, involved 30 patients over the age of 18 who had undiagnosed ILD and required a histopathological diagnosis. Two equal groups were formed from the participants. Group I underwent transbronchial cryobiopsy guided by fluoroscopy, and group II underwent transbronchial forceps biopsy guided by fluoroscopy. Results Laboratory data and spirometry were insignificantly different between both groups. The site of biopsies were insignificantly different between both groups. The procedure took significantly longer in group I than in group II, and the biopsy size was significantly larger (p < 0.05). While there was no significant difference in the incidence of pneumothorax between the two groups, group I also had significantly higher bleeding and diagnostic yield (p < 0.05). Conclusions Transbronchial biopsy guided by fluoroscopy using forceps or cryo technique has great value in ILD cases with non-definitive diagnosis. Transbronchial cryobiopsy has more advantages than transbronchial forceps biopsy regarding sample size, quality, and diagnostic value.